2010
DOI: 10.1371/journal.pone.0013051
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Collagen Fragments Are Significantly Altered in Diabetes: A Link to Pathophysiology

Abstract: BackgroundThe pathogenesis of diabetes mellitus (DM) is variable, comprising different inflammatory and immune responses. Proteome analysis holds the promise of delivering insight into the pathophysiological changes associated with diabetes. Recently, we identified and validated urinary proteomics biomarkers for diabetes. Based on these initial findings, we aimed to further validate urinary proteomics biomarkers specific for diabetes in general, and particularity associated with either type 1 (T1D) or type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 56 publications
1
61
1
Order By: Relevance
“…Urinary peptidome and proteome also suggested that collagen fragments are potential biomarkers for renal fibrosis (407)(408)(409). Global analyses of urinary proteins and peptides could be superior to analyses of single markers (407)(408)(409)(410)(411), and a number of studies have used this approach (412)(413)(414). At the moment, proteomic analyses are not yet feasible for broad clinical application.…”
Section: Serum and Urine Biomarkersmentioning
confidence: 99%
“…Urinary peptidome and proteome also suggested that collagen fragments are potential biomarkers for renal fibrosis (407)(408)(409). Global analyses of urinary proteins and peptides could be superior to analyses of single markers (407)(408)(409)(410)(411), and a number of studies have used this approach (412)(413)(414). At the moment, proteomic analyses are not yet feasible for broad clinical application.…”
Section: Serum and Urine Biomarkersmentioning
confidence: 99%
“…There have been a number of studies, especially using urine, that have developed biomarkers models for a number of different diseases using capillary electrophoresis (CE) and mass spectrometry (MS). Those investigated so far range from renal disorders [16,17] to cardiovascular disease [18] and diabetes [19]. Many of these biomarker profiles have been recorded in a database made up from over 13,000 samples [20].…”
Section: Introductionmentioning
confidence: 99%
“…88 In the largest multicenter study to date, involving 902 participants at ten different centers using capillary electrophoresis coupled mass spectrometry, Maahs et al reported that 131 urinary biomarker candidates were differentially regulated between type 1 and type 2 DM. 89 Specifically, a decrease in urinary level of fragments of collagen α-1 (I) and (III) was found in type 2 DM as compared with type 1 DM. This suggests that a disturbance in the physiologic degradation of the extracellular matrix occurs, perhaps due to decreased activity of certain matrix metalloproteases in diabetes.…”
Section: Urinary Proteomicsmentioning
confidence: 87%
“…90,91 On the other hand, fragments of fibrinogen α and β were increased in type 2 DM as compared with type 1 DM. 89 Other proteins sequenced include fragments of α-1 antitrypsin, membrane-associated progesterone receptor component 1, and uromodulin. This panel of biomarkers distinguished type 1 DM from type 2 DM in an independent validation set of normoalbuminuric patients with 88% (95% confidence interval 81%-94%) accuracy and in patients with impaired renal function with 85% (95% confidence interval 81%-88%) accuracy.…”
Section: Urinary Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation